2022
DOI: 10.1101/2022.03.22.485367
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Marked regional glial heterogeneity in the human white matter of the central nervous system

Abstract: The myelinated white matter tracts of the central nervous system (CNS) are essential for fast transmission of electrical impulses and are commonly affected in neurodegenerative diseases. However, these often uniquely human diseases differentially affect white matter regions, at various ages and between males and females, and we hypothesised that this is secondary to physiological variation in white matter glia with region, age and sex. Using single nucleus RNA sequencing of healthy human post-mortem samples, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 85 publications
1
8
0
Order By: Relevance
“…As noted, we did not observe such upregulation of immune‐related markers in microglia of SC versus such cells from other regions The observed difference between MOLs and microglia may be due to the specific interactions of OL lineage cells and neuronal subtypes in local microenvironments across different CNS regions as suggested by (Zonouzi et al, 2019). Seeker et al detected the expression of an immune‐gene expressing OL cluster in the human cervical spinal cord (Seeker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As noted, we did not observe such upregulation of immune‐related markers in microglia of SC versus such cells from other regions The observed difference between MOLs and microglia may be due to the specific interactions of OL lineage cells and neuronal subtypes in local microenvironments across different CNS regions as suggested by (Zonouzi et al, 2019). Seeker et al detected the expression of an immune‐gene expressing OL cluster in the human cervical spinal cord (Seeker et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous expression of ATP11B in ECs does not relate to vessel type, as this occurs in the same vessel section, and all vessels studied are very small (by definition) and capillaries. We capitalised on our Human Cell Atlas single nuclei RNAsequencing data in adult human brain tissue [48] subsetting for ECs, categorising them of arteriole, capillary and venule origin using scSorter [21], and visualising ATP11B expression on an individual cell basis. Here, we found clear heterogeneity of ATP11B RNA expression in human brain small vessel ECs (Fig.…”
Section: Atp11b Is Expressed By Many Brain Cells In Vivo In a Heterog...mentioning
confidence: 99%
“…The density of gold particles per volume of EC profile (particles/µm 3 ) shows that one of the five ECs (EC5, red) has a far lower density of ATP11B-gold than the other four ECs (ECs 1-4; green, yellow, cyan, magenta) by a factor of between 9.5 and 14, compared to the level of background gold labelling seen in the nuclei (blue) of ECs 1 and 4 (green/magenta); 2.5 particles/µm 3 ). e Single nucleus heterogeneous expression of ATP11B transcript from snRNAseq in human adult CNS ECs, categorised into arteriole, capillary and venules [48]. f Heterogeneous expression of ATP11B (white) in human brain ECs of a vessel, yellow arrows indicate no ATP11B expression, green arrows indicate ATP11B expression.…”
Section: The Atp11bko Rat Is Normotensivementioning
confidence: 99%
“…Examination of mouse single‐cell RNAseq data from the Dropviz dataset (Saunders et al, 2018 ) showed higher expression of complement genes and Cd74 in cerebellar microglia (Figure S5 ). A recent single nuclear RNAseq profiling of glial cells in the human CNS showed more expression of CD74 and HLA‐DRA in caudal regions compared to BA4 primary motor cortex (Seeker et al, in press ) indicating cross‐species conservation of regional microglial heterogeneity and across analytical platforms. We next validated spatial RNAseq profiles of pig microglia by performing in situ hybridization on the highly abundant C3 gene that was enriched in cerebellar microglia.…”
Section: Resultsmentioning
confidence: 99%